In Situ U–Pb Monazite and Xenotime Geochronology of the Abra Polymetallic Deposit and Associated Sedimentary and Volcanic Rocks, Bangemall Supergroup, Western Australia - Rasmussen, Birger; Fletcher, Ian; Muhling, J.; Gregory, Courtney; Thorne, A.; Cutten, H.; Pirajno, F.; Hell, A. (Geological Survey of Western Australia (GSWA), 2010)
Abra is a major lead–silver–copper–gold deposit within the Bangemall Supergroup that has a total indicated and inferred resource estimate of 93 million tonnes at 4.0% lead and 10 g/t silver and 14 million tonnes at 0.6% copper and 0.5 g/t gold. The mineralization lies within the upper part of the locally defi ned Gap Well Formation, and in the lower part of the overlying West Creek Formation. These units correlate respectively with the Irregully and lower Kiangi Creek Formations of the Edmund Group.The Abra deposit is characterized by a funnel-shaped brecciated zone, interpreted as a breccia feeder-pipe, overlain by stratabound mineralization made up of the Red Zone, an underlying Black Zone, and a stringer (feeder) zone. The Red Zone is characterized by banded jaspilite, hematite, galena, pyrite, quartz, abundant barite, and siderite. The Black Zone consists of veins and rhythmically banded Pb, Zn, and minor Cu sulfi des, laminated and/or brecciated hematite, magnetite, Fe-rich carbonate, barite, and scheelite.In situ Sensitive high-resolution ion microprobe (SHRIMP) U–Pb geochronology of detrital zircon, monazite, and xenotime in sandstones from the Abra deposit yields a range of dates from c. 2450 Ma to c. 1675 Ma, consistent with results from previous detrital zircon studies. SHRIMP dating of hydrothermal monazite from the Abra deposit suggests that a mineralization event occurred at c. 1385 Ma. The presence of c. 1465 Ma metamorphic/hydrothermal monazite in sandstones from Abra indicates that the host rocks are older and therefore belong to the Edmund Group. SHRIMP geochronology of xenotime extracted from the Tangadee Rhyolite, which outcrops within the lower Kiangi Creek Formation close to the Abra deposit, yields two main age components corresponding to oscillatory-zoned cores and unzoned rims. The cores are interpreted as magmatic in origin and indicate a possible eruption age of c. 1235 Ma, whereas the rims are interpreted to record a later hydrothermal event at c. 1030 Ma. If this interpretation is correct, then the sedimentary succession containing the rhyolite is younger than the Edmund Group (<1640 Ma and >1465 Ma), and may belong to the basal Collier Group (<1465 Ma and >1070 Ma) although the geological setting does not support this.